Solve 3*z - 9 = 2*g, 4*z = 2*g - z + 19 for g.
3
Solve -3*v - 14 = i, -12*v = i - 15*v - 16 for i.
1
Solve -s + 2*z = 3, -3*z = -2*s - 8*z + 12 for s.
1
Solve -3*k = -5*r - 9 + 22, -r - k + 9 = 0 for r.
5
Solve -c + 23 = 5*x + 4, 5*c = -x + 23 for x.
3
Solve 4*k + a - 1 + 4 = 0, 9 = -2*k + a for k.
-2
Solve -q = 3*s - 6, -26 = -4*s - 5*q - 29 for s.
3
Solve -4*u - 6 = 4*w + u, -5*u = w + 9 for w.
1
Solve -f + 4*d - 5*d - 10 = 0, 5*f = 4*d - 5 for f.
-5
Solve 2*b + 8 = 4*d, -3*d - 5*b + 59 = 14 for d.
5